The Evaluation Of Textbook Entitled "Headline English 1" For The Seventh Year Of Junior High School - Rizky, Hanif Safika, Drs. Djoko Srijono, M.Hum, Mauly Halwat Hikmat, Ph. D (2014)
This research paper aims at finding out whether the English textbook used for the seventh year of Junior High School entitled Headline English 1 is compatible or not with criteria of good materials design suggested by Rajan. This research is descriptive research. In collecting data, the writer used documentary analysis. The data were analyzed by (1) presenting the materials (2) comparing the materials (3) judging whether the materials of English textbook is appropriate with criteria of good materials design suggested by Rajan or not (4) drawing conclusion. The result shows that the percentage of the compatibility of language skills developed in the textbook is 81,82%. It means the textbook is good in developing language skills materials as suggested by Rajan. The language skills which are developed in the textbook involve: 1) the compatibility of the listening materials are 72,73% or good. 2) the compatibility of the speaking materials are 81,82% or good. 3) the compatibility of reading materials are 81,82% or good and 4) the compatibility of writing materials are 90,91% or excellent. This research implies the textbook entitled "Headline English1" for the seventh year of Junior High School provides good materials to support teaching-learning process. The materials design in this textbook facilitates the students for developing the competencies.